Difficulties that Advanced Intensive English I student of The Bachelor of Arts in English with emphasis in teaching face to produce accurate and fluent oral english discourse at the Department of Foreign Languages of The University of El Salvador, year 2015 - Martínez Luna, Adiel Isaí; Ruiz Molina, José Enrique; Valle Valle, Roberto Vladimir; Contreras Cárcamo, Mauricio Salvador; Landaverde Castillo, Manuel Alexander (San Salvador, El Salvador : Universidad de El Salvador, 2016)
Speaking English is a difficult task: some experts state that some people understand the language and know a lot about its grammar and lexicon, but when they have to speak, they seem to be at a loss for words. This is a problem that other people have noticed as well. For example, according to Tatham and Morton (2006: 273) many people report that they can understand a language but they cannot speak it. There are also other countries where people experience the same phenomenon; for example, in the Japanese context, it seems that many people have difficulties in speaking English. This is clearly a problem, because the aim of English language education is to provide learners with the capabilities to understand the language and the ability to both write and speak it. If learners are not able to speak English, this aim has not been fully achieved. Thus, it is necessary to study this issue in order to discover if people indeed have problems with speaking, and if they do, what kind of difficulties and what activities are being used in class to overcome them. Of course, not all learners struggle with speaking. However, since there are some people who do have problems with speaking, there is a good reason to research the matter. More insight into this might be able to help develop the teaching of English speech production and thus the abilities of English learners. This study attempts to acquire useful information about this problem by gathering, analyzing, and interpreting the data collected through the use of some methods as surveys, interviews, and checklists. Students from Advanced Intensive English I of the Bachelor of Arts in English at the Department of Foreign Languages of the University of El Salvador, year 2015 were chosen because they are more likely to have experience of using English for a longer period of time. The aims are to identify the main difficulties they have in speaking English and the types of activities teachers are using to enhance and overcome them.
Incluye anexos.
Tesis para optar al titulo de -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Univesidad de El Salvador, San Salvador, 2016
Bibliografía : hojas 109-111